‘ZOUFAN’ AS A ‘TREE HOLE’ FOR ONLINE SHARING OF DEPRESSION: PARTICIPATION PATTERNS, DOMINANT TOPICS AND LINGUISTIC FEATURES - Chen Yating (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The concept of ‘tree hole’ in social media has provided a disinhibited space for depressed individuals to communicate their depressive feelings, emotions and experiences freely. Its proliferation underscores an increasing need for such online spaces. However, their operational mechanisms, content dynamics, and implications for mental health remain under-explored, especially in the Mainland Chinese context. This study describes and interprets what is going on under ‘Zoufan’, the largest ‘tree hole’ on Weibo in China, by analyzing the patterns of online community engagement concerning discussions on depression. In an overarching project, a total of 67,614 comments under the last farewell post of ‘Zoufan’ were collected and compiled for an overview of the user’s participation patterns. This paper draws upon a set of data manually coded on the selected topics and a fine-grained analysis of linguistic features. The findings indicate a limited interest among selected users in interacting with others, with most of the content focusing on their adverse emotional states and the difficulties they face within interpersonal relationships. Moreover, the expressions contain a strong sense of negation and inhibition, often conveyed through fragmented narratives. The implications of this study help stakeholders, especially family members, educators, and mental health workers, to better understand the mental health outcomes of participation in online depression sharing. This, in turn, facilitates a more nuanced approach to addressing depression both online and in real-life interventions.